2016
DOI: 10.1007/978-3-319-30139-6_19
|View full text |Cite
|
Sign up to set email alerts
|

Shortest Reconfiguration of Sliding Tokens on a Caterpillar

Abstract: Suppose that we are given two independent sets I b and Ir of a graph such that |I b | = |Ir|, and imagine that a token is placed on each vertex in I b . Then, the sliding token problem is to determine whether there exists a sequence of independent sets which transforms I b into Ir so that each independent set in the sequence results from the previous one by sliding exactly one token along an edge in the graph. The sliding token problem is one of the reconfiguration problems that attract the attention from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The algorithm is constructive, and the sequence itself can be output in O(n 2 ) time. As mentioned in [26], the number of required token-slides in a sequence can be Ω(n 2 ), hence our algorithm is optimal for the number of token-slides. Note: Recently, it is announced that the Shortest Sliding Token problem on a tree can be solved in polynomial time by Sugimori [23].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The algorithm is constructive, and the sequence itself can be output in O(n 2 ) time. As mentioned in [26], the number of required token-slides in a sequence can be Ω(n 2 ), hence our algorithm is optimal for the number of token-slides. Note: Recently, it is announced that the Shortest Sliding Token problem on a tree can be solved in polynomial time by Sugimori [23].…”
Section: Introductionmentioning
confidence: 95%
“…The Sliding Token problem on a tree can be solved in linear time [6]. Polynomial-time algorithms for the Shortest Sliding Token problem were first investigated in [26]. In [26], the authors gave polynomial-time algorithms for solving Shortest Sliding Token when the input graph is either a proper interval graph, a trivially perfect graph, or a caterpillar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results on INDEPENDENT SET RECONFIGURATION have not been confined to reachability. Polynomial-time algorithms have been developed for shortest transformation under TS for proper interval graphs, trivially perfect graphs, and caterpillars [58] (though NP-hard in general for all reconfiguration steps [17]), for connectivity under TS for interval graphs [56] and under TAR for cographs [55], and for finding an actual reconfiguration sequence under TS for trees (as an extension of the reachability algorithm) [59]. It has also been shown that there is an infinite family of instances on paths for which the length of the reconfiguration sequence is at least quadratic in the number of vertices [59]; in contrast, for every yes-instance of reachability on cographs, there is a bound on the length of the reconfiguration sequence [42] as well as a bound on the diameter for claw-free graphs [57].…”
Section: Analysis Using Graph Classes For Independent Setmentioning
confidence: 99%
“…Results on INDEPENDENT SET RECONFIGURATION have not been confined to reachability. Polynomial-time algorithms have been developed for shortest transformation under TS for proper interval graphs, trivially perfect graphs, and caterpillars [58] (though NP-hard in general for all reconfiguration steps [17]), for connectivity under TS for interval graphs [56] and under TAR for cographs [55], and for finding an actual reconfiguration sequence under TS for trees (as an extension of the reachability algorithm) [59]. It has also been shown that there is an infinite family of instances on paths for which the length of the reconfiguration sequence is at least quadratic in the number of vertices [59]; in contrast, for every yes-instance of reachability on cographs, there is a bound on the length of the reconfiguration sequence [42] as well as a bound on the diameter for claw-free graphs [57].…”
Section: Analysis Using Graph Classes For Independent Setmentioning
confidence: 99%